2007
DOI: 10.1039/b615225b
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory study of twelve-atom germanium clusters: conflict between the Wade–Mingos rules and optimum vertex degrees

Abstract: Density functional theory (DFT) at the hybrid B3LYP level has been applied to Ge(12)(z) bare germanium clusters (z = -6, -4, -2, 0, +2, +4, +6) starting from 11 initial configurations. The Wade-Mingos rules are seen to have limited value in rationalizing the results since they frequently require vertex degrees higher than the optimum vertex degree of 4 for germanium. Thus the expected I(h) regular icosahedron is no longer the global minimum for Ge(12)(2-) although it remains a low energy structure for Ge(12)(2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 32 publications
0
27
0
2
Order By: Relevance
“…Die höchsten besetzten MOs der [E n ] 2− ‐Cluster weisen dagegen lone‐pair‐Charakter auf. Das HOMO von [B 12 H 12 ] 2− ist der oberflächenbindende g u ‐Satz,99, 307 und das HOMO der [E 12 ] 2− ‐Anionen ist der h g ‐Satz (E=Si,307 Ge,308 Sn99, 309) oder der t 1u ‐Satz (E=Pb100, 300, 310) mit lone‐pair‐Charakter.…”
Section: Theoretische Untersuchungenunclassified
See 1 more Smart Citation
“…Die höchsten besetzten MOs der [E n ] 2− ‐Cluster weisen dagegen lone‐pair‐Charakter auf. Das HOMO von [B 12 H 12 ] 2− ist der oberflächenbindende g u ‐Satz,99, 307 und das HOMO der [E 12 ] 2− ‐Anionen ist der h g ‐Satz (E=Si,307 Ge,308 Sn99, 309) oder der t 1u ‐Satz (E=Pb100, 300, 310) mit lone‐pair‐Charakter.…”
Section: Theoretische Untersuchungenunclassified
“…Strukturoptimierungen für die [E 12 ] 2− ‐Anionen mit E=Si,306, 307, 311, 312 Ge,306, 308, 312 Sn99, 306, 312, 313 und Pb,100, 300, 306, 313 zeigen erwartungsgemäß, dass die ikosaedrische Struktur ( I h ‐Symmetrie) für alle [E 12 ] 2− ‐Cluster einem Grundzustand entspricht. Dieser stellt aber nur für [Sn 12 ] 2− und [Pb 12 ] 2− eindeutig das globale Minimum dar.…”
Section: Theoretische Untersuchungenunclassified
“…However, if the otherwise external lone pairs of the underlying Al 8 cube in Al 8 (µ 8 -Si)(µ 4 -AlCp*) 6 are also counted, then the omnicapped cube in this cluster becomes a 24 + (8)(2) = 40-electron system, which is a favored number using the jellium model. [20,21] The research discussed in this paper extends our DFT studies to clusters with more than 12 vertices in order to study effects of electron count on supraicosahedral cluster geometry. The 14-vertex systems were chosen in preference to the 13-vertex systems because of their higher symmetry and greater variety outside polyhedral borane and carborane chemistry.…”
Section: Introductionmentioning
confidence: 98%
“…The DFT methods used in this work are well established having previously been used by our group to study bare germanium clusters having five to twelve germanium atoms. [22][23][24][25][26][27] …”
Section: Introductionmentioning
confidence: 99%
“…One explanation is that the Cr or W atom is simply too large to fit inside an icosahedral Si 12 cage, and so the prismatic structure, with its larger volume, is preferred. 14,15 Jellium-type models can also be applied in this context, and configurations of 1s 2 1p 6 1d 10 (18 electrons) and 1s 2 1p 6 1d 10 2s 2 (20 electrons) have been invoked to account for the relatively high dissociation energies of Cr@Si 12 and isostructural Fe@Si 12 . [16][17][18] In their initial report, 3 Hiura et al suggested that the stability of W@Si 12 could be rationalised in terms of an 18-electron rule: donation of 12 electrons from the Si 12 cage to the metal raises the electron count to 18, leaving three electrons per Si center to form the three Si-Si bonds.…”
Section: Introductionmentioning
confidence: 99%